Improving saccharification process by pre-swelling of normal maize starch granules for production of sugar and fermented chemicals - Tong, Zhenyu (Kansas State University, 2019)
Partial swelling of granules above the gelatinization temperature was investigated as a strategy to enhance the enzymatic hydrolysis of normal maize starch to glucose. Native and partially swollen starches were hydrolyzed by a granular starch hydrolyzing enzyme (GSHE). After preheated at 70 °C for 30 min, enzyme kinetics study showed a 54% reduction in the Michaelis-Menten constant value (Km), suggesting that preheating increased the affinity of GSHE for the starch granules. Moreover, 94.8% of starch (2% in H₂O, w/w) was converted to glucose after a 24 h saccharification process. This relatively low-temperature process reduced the energy required to completely destroy the starch granules. Preheating at 70 °C, which resulted in partial swelling of starch granules, induced a greater degradation of large molecules, enzymatic erosion of crystallinity and granular structure. In addition, the enzyme resistant fraction could be converted to glucose after cooking. A full conversion of normal maize starch to glucose by GSHE could be achieved. In the saccharification process with a high maize starch concentration (30% in H₂O, w/w), partial swelling starch granules would result in viscosity build-up problem. To overcome that, we used an [alpha]-amylase during heat pretreatment. The viscosity decreased greatly from 2.85×10^6 cP to 12 cP, which was preferable in later saccharification. The heat treatment with [alpha]-amylase at 70 °C partially destroyed crystalline lamellae and maize starch granule structure. By combining [alpha]-amylase in the preheating process and saccharification by GSHE, a two-step enzymatic hydrolysis process was performed. Starch granules were pre-hydrolyzed by [alpha]-amylase at 70 °C for 6 h and followed the addition of GSHE and incubation at 62 °C for 72 h. The two-step enzymatic hydrolysis was more effective than the single hydrolysis at 62 °C and increased the conversion by 25%. More than 93% of total starch could be converted to glucose and the enzyme resistant residue could be further hydrolyzed by conventional cooking method. The two-step enzymatic hydrolysis offered great advantages in the production of glucose syrups and other fermentable chemicals. To further investigate the potential utilization of partially swollen maize starch with GSHE in the production of fermented chemicals, productions of citric acid and ethanol by low-temperature fermentations were studied in both lab-scale and large pilot scale. In the production of citric acid, maize starch (18% in H₂O, w/w) was fermented at 37 °C for 67 h. The initial substrate concentration (18%) was 2% greater than the starch concentration used in the conventional cooking process. The yield of the citric acid was 88%, which was 3% higher than that of conventional cooking production. For ethanol production, maize flour (30% in H₂O, w/w) was fermented at 32 °C for 72 h. The ethanol yield was 92.6%, which was 3.5% higher than that of ethanol produced by the cooking method.
Keywords: Maize Starch Saccharification; Pre-swelling Normal Maize Granule; Granule Starch Hydrolyze Enzyme